Deposition and spatial variation of thoron decay products in a thoron experimental house using the Direct Thoron Progeny Sensors. (30th March 2017) - Mishra, R; Joshi, M; Meisenberg, O; Gierl, S; Prajith, R; Kanse, S D; Rout, R; Sapra, B K; Mayya, Y S; Tschiersch, J
Abstract: Experiments have been carried out using the deposition-based Direct Thoron Progeny Sensors (DTPS) in a thoron experimental house. The objective was to study the thoron decay product characteristics such as the deposition velocities, spatial variability and dependence on aerosol particle concentrations. Since the deposition velocity is an important characteristic in the calibration of the DTPS, it is very important to study its dependence on aerosol concentration in a controlled environment. At low aerosol concentration (1500 particles/cm 3 ) the mean effective deposition velocity was measured to be 0.159 ± 0.045 m h −1 ; at high aerosol concentration (30 000 particles/cm 3 ) it decreased to 0.079 ± 0.009 m h −1 . The deposition velocity for the attached fraction of the thoron decay products did not change with increasing aerosol concentration, showing measurement results of 0.048 ± 0.005 m h −1 and 0.043 ± 0.014 m h −1, respectively. At low particle concentration, the effective deposition velocity showed large scattering within the room at different distances from center. The attached fraction deposition velocity remained uniform at different distances from the wall. The measurements in the thoron experimental house can be used as a sensitivity test of the DTPS in an indoor environment with changing aerosol concentration. The uniform spatial distribution of thoron decay products was confirmed within the experimental house. This indicates that direct measurement of thoron decay product concentration should be carried out instead of inferring it from thoron gas concentration, which is very inhomogeneous within the experimental house.